Development of seismic fragility surfaces for reinforced concrete buildings by means of nonlinear time-history analysis. - Seyedi, D.M (Earthquake engineering & structural dynamics.)
Fragility curves are generally developed using a single parameter to relate the level of shaking to the expected structural damage. The main goal of this work is to use several parameters to characterize the earthquake ground motion. The fragility curves will, therefore, become surfaces when the ground motion is represented by two parameters. To this end, the roles of various strong motion parameters on the induced damage in the structure are compared through nonlinear time history numerical calculations. A robust structural model that can be used to perform numerous nonlinear dynamic calculations, with an acceptable cost, is adopted. The developed model is based on the use of structural elements with concentrated nonlinear damage mechanics and plasticity-type behavior. The relations between numerous ground motion parameters, characterizing different aspects of the shaking and the computed damage are analyzed and discussed. Natural and synthetic accelograms were chosen/computed based on a consideration of the magnitude-distance ranges of design earthquakes. A complete methodology for building fragility surfaces based on the damage calculation through nonlinear numerical analysis of multi-degree of freedom systems is proposed. The fragility surfaces are built to represent the probability that a given damage level is reached (or exceeded) for any given level of ground motion characterized by the two chosen parameters. The results show that an increase from one to two ground motion parameters leads to a significant reduction in the scatter that an increase from one to two ground motion parameters leads to a significant reduction in the scatter in the fragility analysis and allows the uncertainties related to the effect of the second ground motion parameter to be accounted for within risk assessments.